Comparing two reliable multicast protocols for mobile computing - Ribeiro,Mateus de Freitas (2003)
As networks with mobile devices becorne commonplace, many new applications for those networks arisc, including some that require coordination among groups of mobile clients. One basic tool for implementing coordination is reliable multicast, where delivery of a multicast message is atomic, i.e. cither all or none of the group members deliver the message. While several multicast protocols have been proposed for mobile networks, only a few works have considered reliable multicats. In this paper we present and compare two protocols based on Two-Phase-Commit that implement reliable multicast for structured mobile networks. Protocol iAM²C is a variant of protocol AM2C that employs a two-level hierarchical location management scheme to locate and route messages to the mobile hosts addressed by a multicast. Although hierarchical location management is not new in the context of mobile and cellular networks, we are unaware of any other work which combines hierarchical location management with protocols for reliable multicast. We have prototyped, simulated and evaluated both protocols using the MobiCS simulation enviromment. Our experiments indicate that despite some overhead incurred by the location management and the additional level of message redirection, iAM2C is more efficient than the AM² C protocol and scales well with the size of the wired network infra-structure.